Determination of antimony in plant and peat samples by hydride generation-atomic fluorescence spectrometry (HG-AFS) - Chen, Bin; Krachler, Michael; Shotyk, William (Journal of analytical atomic spectrometry, 2003)
A robust and sensitive analytical procedure for the determination of Sb in plant and peat samples using hydride generation-atomic fluorescence spectrometry (HG-AFS) has been developed. The hydride generation of Sb was carried out by using 1% (m/v) of NaBH4 and 4 mol l−1 HCl. The analytical procedure was critically evaluated by analysing five certified plant reference materials (BCR CRM 281 Rye Grass, CTA-VTL-2 Virginia Tobacco Leaves, GBW 07602 Bush Branches and Leaves, SRM 1547 Peach Leaves and SRM 1515 Apple Leaves) and two in-house peat reference materials. The accuracy and precision (<3%) of the developed procedure was evaluated by the determination of Sb in certified reference materials, two in-house reference materials, and showed good agreement with the reference and information values. Prior to HG-AFS, 200 mg aliquots of dried samples were digested with 3 ml nitric acid, 0.5 ml hydrogen peroxide and 0.1 ml tetrafluoroboric acid (HBF4) using closed-pressurized digestion in a microwave oven. The efficiency of applying HBF4 for destroying silicates in the samples was also investigated. The digests of the samples were first diluted to 10 ml using high purity water, subsequently mixed with 1 ml of 50 g l−1L-cysteine for the pre-reduction of Sb(V) in the digests, and finally diluted to 50 ml using 4 mol l−1 hydrochloric acid for measurement. A solution detection limit of 8 ng l−1 was obtained using the optimised experimental conditions which corresponds to a method detection limit of 2 ng g−1 in solid peat: this detection limit is far lower than those previously reported for this element using the identical HG-AFS instrument. The newly developed analytical procedure has been applied to the determination of Sb in ancient peat samples collected from remote Scottish peat bogs. The high sea salt content of these peat samples caused no matrix interferences. Comparison of the results obtained using HG-AFS with instrumental neutron activation analysis (INAA) data obtained previously shows that the lower limits of detection of INAA are unsuitable for measuring Sb in pre-anthropogenic samples.